Risk of Reactivation of Hepatitis B Virus (HBV) and Tuberculosis (TB) and Complications of Hepatitis C Virus (HCV) Following Tocilizumab Therapy: A Systematic Review to Inform Risk Assessment in the COVID-19 Era - Campbell, Cori; Andersson, Monique I.; Ansari, M. Azim; Moswela, Olivia; Misbah, Siraj A.; Klenerman, Paul; Matthews, Philippa C. (Frontiers in Medicine, 2021)
Objectives: Tocilizumab (TCZ), an IL-6 receptor antagonist, is used in the treatment of severe COVID-19 caused by infection with SARS-CoV-2. However, TCZ complications include reactivation of tuberculosis (TB) or hepatitis B virus (HBV), and worsening of hepatitis C virus (HCV). We set out to assimilate existing data for these complications, in order to help inform evidence-based risk assessments for the use of TCZ, and thus to reduce the risk of preventable complications. Methods: We searched the global WHO database of Individual Case Safety Reports (ICSRs) and adverse drug reactions (ADRs) (‘VigiBase’) and undertook a systematic literature review, in accordance with PRISMA guidelines. We generated mean cumulative incidence estimates for infection complications. Results: Mean cumulative incidence of HBV and TB were 3.3% and 4.3%, respectively, in patients receiving TCZ. Insufficient data were available to generate estimates for HCV. These estimates derive from heterogeneous studies pre-dating SARS-CoV-2, with differing epidemiology and varied approaches to screening and prophylaxis, so formal meta-analysis was not possible. Conclusions: We underline the need for careful individual risk assessment prior to TCZ prescription, and present an algorithm to guide clinical stratification. There is an urgent need for ongoing collation of safety data as TCZ therapy is used in COVID.